2008
DOI: 10.1152/ajpcell.00333.2007
|View full text |Cite
|
Sign up to set email alerts
|

Connective tissue growth factor inhibits adipocyte differentiation

Abstract: Adipocyte differentiation is a key process implicated in the pathogenesis of obesity and insulin resistance. Its regulation is triggered by a cascade of transcription factors, including the CCAAT/enhancer binding proteins (C/EBPs) and peroxisome proliferator-activated receptor-γ (PPARγ). Growth factors such as transforming growth factor-β1 (TGF-β1) are known to inhibit adipocyte differentiation in vitro, via the C/EBP pathway, and in vivo, but whether a downstream mediator of TGF-β1, connective tissue growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
82
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 63 publications
14
82
1
Order By: Relevance
“…We have shown previously that, like TGF-␤1, CCN-2 is downregulated during adipocyte differentiation in vitro, and in this system exogenously added CTGF was effective in the inhibition of the adipocyte differentiation program (55). Our initial observations in chow-fed mice also showed that CCN-2 expression was twofold higher in the epididymal fat depot compared with the subcutaneous fat depot (55). Because a lower level of differentiation of fat cells in the epididymal depot was associated with the development of insulin resistance, the higher basal expression of CCN-2 at this site implicated a possible role for this protein in the negative regulation of adipocyte differentiation in vivo (55).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…We have shown previously that, like TGF-␤1, CCN-2 is downregulated during adipocyte differentiation in vitro, and in this system exogenously added CTGF was effective in the inhibition of the adipocyte differentiation program (55). Our initial observations in chow-fed mice also showed that CCN-2 expression was twofold higher in the epididymal fat depot compared with the subcutaneous fat depot (55). Because a lower level of differentiation of fat cells in the epididymal depot was associated with the development of insulin resistance, the higher basal expression of CCN-2 at this site implicated a possible role for this protein in the negative regulation of adipocyte differentiation in vivo (55).…”
mentioning
confidence: 58%
“…It is a multifunctional protein produced by a variety of cells, including endothelial cells, fibroblasts, cartilaginous cells, smooth muscle cells, and fat cells (16,24,25,27,28,41,54). We have shown previously that, like TGF-␤1, CCN-2 is downregulated during adipocyte differentiation in vitro, and in this system exogenously added CTGF was effective in the inhibition of the adipocyte differentiation program (55). Our initial observations in chow-fed mice also showed that CCN-2 expression was twofold higher in the epididymal fat depot compared with the subcutaneous fat depot (55).…”
mentioning
confidence: 69%
“…In some cases differing CCN family members have been shown to have balancing, and antagonistic cell and tissue effects; for example, CCN3 may suppress CCN1 and CCN2-dependent activities (Riser et al 2009;Perbal 2013). We have previously shown that rhTGF-β1 induces CCN2 in adipocyte differentiation (Tan et al 2008). Future studies will be required to examine whether the CCN family of proteins are differentially regulated in fat cell differentiation, including by TGF-β and its downstream pathways, and whether effects of differing CCN proteins are complementary or antagonistic with eachother in FCD.…”
Section: Discussionmentioning
confidence: 99%
“…This process occurs via a range of temporal transcriptional cues, ultimately resulting in a mature adipocyte characterised by a unilocular lipid droplet (McLennan et al 2004;Tan et al 2008). These morphological and functional changes result from alterations in the expression and organisation of the extracellular matrix and components of cytoskeleton in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
“…RNA was then reverse transcribed to cDNA using Random Hexamer Primer (Invitrogen) and SuperScript III Reverse Transcriptase (Invitrogen). The resulting cDNA was analyzed by quantitative real-time PCR using Rotor Gene 6000 (Corbett Research), using SYBR green as fluorescence dye, as described previously (44). The following sequence-specific primers were used for rat CTGF, BNP, ␤-MHC, rat and mouse ANP, and ␣-SKA and 18s mRNA expression.…”
Section: Methodsmentioning
confidence: 99%